She's dating the gangster - Bernardino, Bianca B. (Summit Publishing Company, Inc., 2013)
"He's mean, he's rude, he gets on her nerves and he's the love of her life. It all starts when 17-year-old Athena Dizon unwittingly plays a trick on resident heartthrob and bad boy, Kenji de los Reyes. All of a sudden, she finds herself pretending-unwillingly at that-to be his girlfriend to make his ex jealous. Now, not only does she have to deal with dirty looks from the girls in school who want Kenji for themselves, but her supposed boyfriend is getting on her nerves. He's hotheaded, never seems to agree with her on anything-and everything about him screams "gangster". Has Athena gotten herself into more trouble than she can handle? Or has she actually found herself a boy she can call hers-"gangster" be damned?"--Amazon.com.